Research and Reflections on Southeast Asian American Education and Advancement (Purdue University Press, 2026)
This book is in commemoration of the twentieth anniversary of the Journal of Southeast Asian American Education and Advancement (JSAAEA) and the fiftieth anniversary of Southeast Asian American refugee resettlement in the United States. Pivotal research articles, reviews, and creative works from past issues of JSAAEA have been selected for this volume to document the history and experiences of Cambodian, Laotian, Hmong, and Vietnamese Americans since initial refugee resettlement began in the United States in 1975, as well as the experiences of more recent Southeast Asian immigrant and refugee groups. Reviews of academic books, novels, memoirs, children’s books, and motion pictures further highlight Southeast Asian American perspectives and experiences. Creative works, including poetry and short stories by Cambodian, Laotian, Hmong, Vietnamese, Thai, and Burmese American writers, provide additional and often intimate insights and reflections on the Southeast Asian American experience.